1999
DOI: 10.1088/0264-9381/16/11/303
|View full text |Cite
|
Sign up to set email alerts
|

Causal continuity in degenerate spacetimes

Abstract: A change of spatial topology in a causal, compact spacetime cannot occur when the metric is globally Lorentzian. One can however construct a causal metric from a Riemannian metric and a Morse function on the background cobordism manifold, which is Lorentzian almost everywhere except that it is degenerate at each critical point of the function. We investigate causal structure in the neighbourhood of such a degeneracy, when the auxiliary Riemannian metric is taken to be Cartesian flat in appropriate coordinates.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 26 publications
2
64
0
Order By: Relevance
“…We then show that the above conjecture implies the k-causal continuity in the spacetime with the degeneracies is equivalent to the causal continuity of the spacetime with the degeneracies excised. We also show that, independently of whether the conjecture holds, index 1 and n − 1 Morse spacetimes are k-causally discontinuous, as expected [7,8].…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…We then show that the above conjecture implies the k-causal continuity in the spacetime with the degeneracies is equivalent to the causal continuity of the spacetime with the degeneracies excised. We also show that, independently of whether the conjecture holds, index 1 and n − 1 Morse spacetimes are k-causally discontinuous, as expected [7,8].…”
Section: Introductionsupporting
confidence: 58%
“…In particular, one can construct a rather general class of such spacetimes which contain only isolated degeneracies. These "Morse spacetimes" were studied in detail in [6,16,7] within the Sum-Over-Histories approach to quantum gravity, and can be defined in any topological cobordism, as follows.…”
Section: Causal Continuity In Morse Spacetimesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of papers Sorkin, Dowker et.al. [7,8,9] analyzed possible topology changes. In particular they showed that causal discontinuity occurs if and only if the Morse index is 1 or n − 1, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, there is no barrier to sprinkling into manifolds with spatial topology change, as long as it is degeneracy of the metric at a set of isolated points that enables topology change, and not the existence of closed timelike curves (one of these conditions must exist for topology change to occur, see e.g. [48] and references therein) -and in this discrete theory there is no problem with characterising the set of histories. For those who believe that topology change will be necessary in quantum gravity [11,49], this is important.…”
Section: Reconstructing the Continuummentioning
confidence: 99%